Arduino based water level detector / Siti Hajar Mohd Nasir and Aimy Athirah Mat Ali - Mohd Nasir, Siti Hajar; Mat Ali, Aimy Athirah (2015)
The project is actually an alternative of the existing water level detector in the market. The main idea of this project is to invent a new measuring device that resemble with the advance measuring devices in terms of its operation, but with lower production cost. Based on this project, it's detecting the level of water in container which is in to level low and high. Arduino is used as microcontroller to detect the depth of water. Different color of led represent each of water level. LED turn on when its reach certain depth of water. When low level water (red LED ON), relay will switch the pump to let the water flow into container and tank. When the water reach at high level (green LED on), relay will switch the pump to stop the water from entering the tank and container. The water flow to container will rotate by time.